2021
DOI: 10.22603/ssrr.2020-0112
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Spinal Canal Stenosis from the Perspective of Locomotive Syndrome and Metabolic Syndrome: A Narrative Review

Abstract: Patients with lumbar spinal canal stenosis (LSS) have impaired activities of daily living because of pain or motor paralysis, but no effective preventive treatment is currently available. The number of patients with LSS is predicted to continually increase as the average age of the global population increases. To provide a conceptual framework for improving healthy life expectancy, the Japanese Orthopaedic Association introduced the concept of locomotive syndrome, to which LSS is related. Ours and other studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…It is apparent that there are coexisting, interwoven, collective and likely compounding factors that predispose to SEL. This has been a focus of recent studies and metabolic syndrome is postulated to be the connecting link [ 1 , 5 , 18 , [22] , [23] , [24] , [25] , [26] , [27] ]. Based on the National Health and Nutritional Examination Survey (NHANES) data, it has been estimated that at least 68 million U.S. adults meet the criteria for the metabolic syndrome and the trend only seems to be increasing [52] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is apparent that there are coexisting, interwoven, collective and likely compounding factors that predispose to SEL. This has been a focus of recent studies and metabolic syndrome is postulated to be the connecting link [ 1 , 5 , 18 , [22] , [23] , [24] , [25] , [26] , [27] ]. Based on the National Health and Nutritional Examination Survey (NHANES) data, it has been estimated that at least 68 million U.S. adults meet the criteria for the metabolic syndrome and the trend only seems to be increasing [52] .…”
Section: Discussionmentioning
confidence: 99%
“…This has been a focus of recent studies and metabolic syndrome is postulated to be the connecting link. 1,5,18,[22][23][24][25][26][27] Based on the National Health and Nutritional Examination Survey (NHANES) data, it has been estimated that at least 68 million U.S. adults meet the criteria for the metabolic syndrome and the trend only seems to be increasing. 52 It has been observed that the clinical findings associated with metabolic syndrome exist more frequently in SEL patients than would be expected by chance alone and that this accretion is of clinical importance.…”
Section: Metabolic Syndromementioning
confidence: 99%
See 2 more Smart Citations
“…5 In addition, according to recent studies, surgical treatment improves musculoskeletal function in elderly patients with LSS. 6 Previous reports have shown that significant cause of LSS include degenerative changes of spinal components such as hypertrophy of the ligamentum flavum, formation of degenerative osteophytes, and intervertebral disk (IVD) degeneration 7 ; however, the time-dependent changes in those components are still unclear. IVD degeneration, a significant cause of LSS, increases with age and predisposes affected individuals to the low back pain (LBP).…”
mentioning
confidence: 99%